Genetic mapping of ossification of the posterior longitudinal ligament of the spine. - Koga, H (1998)
Ossification of the posterior longitudinal ligament of the spine (OPLL) is recognized as a common disorder among Japanese and throughout Asia. Estimates of its prevalence are in the range of 1. 9%-4.3%. Although its etiology is thought to involve a multiplicity of factors, epidemiological and family studies strongly implicate genetic susceptibility in the pathogenesis of OPLL. In this study we report an identification of a predisposing locus for OPLL, on chromosome 6p, close to the HLA complex. The evidence for this localization is provided by a genetic-linkage study of 91 affected sib pairs from 53 Japanese families. In this sib-pair study, D6S276, a marker lying close to the HLA complex, gives evidence for strongly significant linkage (P = .000006) to the OPLL locus. A candidate gene in the region, that for collagen 11A2, was analyzed for the presence of molecular variants in affected probands. Of 19 distinct variants identified, 4 showed strong statistical associations with OPLL (highest P = .0004). These observations of linkage and association, taken together, show that a genetic locus for OPLL lies close to the HLA region, on chromosome 6p.